Glenohumeral and hip range of motion in youth softball athletes - Friesen, K.; Downs, J.; Wasserberger, K.; Shannon, D.; Oliver, G. D. (International Journal of Sports Medicine, 2020)
The purpose of this study was to compare measures of bilateral shoulder and hip range of motion (ROM) between youth softball pitchers and position players. Fifty-two youth softball athletes (12.7±2.1 yrs.; 160.28±10.98 cm; 59.31±15.07 kg) participated. Bilateral hip and shoulder ROM were measured among pitchers (n=29) and position players (n=23). A 2 (pitcher/position player) × 2 (dominant/non-dominant) ANOVA was performed for both internal and external rotation ROM for the shoulder and hip. Paired sample t-tests were also conducted to examine side-to-side differences in total ROM. Data revealed a significant interaction between position and side dominance. Specifically, position players have significantly more non-dominant shoulder external rotation ROM (106.92°± 9.14°) than pitchers (100.12°± 11.21°). There were no significant differences between throwing and non-throwing sides. It is important that coaches and clinicians are aware of these adaptations between overhand and underhand throwing in order to properly develop conditioning and rehabilitation programs to alleviate injury susceptibility and cater to position-specific demands. Additionally, the current data suggest many of the functional adaptations seen within older populations are not fully developed until after youth.